Sacral nerve stimulation for fecal incontinence. (September 2012) - Skull, Angela; Hull, Tracy L
Fecal incontinence (FI), which can severely affect a person's quality of life, is a difficult problem to treat. For some patients, limited management options exist. Sacral nerve stimulation, also known as sacral neuromodulation, although long established for urinary incontinence, has gained acceptance in treating FI. One unique aspect is that the procedure is performed in two stages. During the first stage, a temporary lead is inserted into the S3 sacral foramen and the patient can monitor improvement before a permanent device is implanted. While this procedure has proven to be effective for treating FI, it is also attractive owing to the low morbidity and low infection risk reported in the literature.